Virtual simulators as a teaching - learning strategy at SENA - Guerrero Vergel, Rene Alexander
The growth on the market of the use of information technologies as a support to the training process shows theinterest that has been generated in educational institutions to manage computer-mediated learning, findingin technologies a valuable resource for expanding coverage and generating new scenarios where learning isforged. However, the implementation of technological resources is limited as it is often done intuitively adjustedto a curriculum, to the teacher’s perception and framed in traditional content, limited by the tools that avirtual platform can offer. The work submitted pretends to show the development of the Virtual Business Simulatorof Administrative and Accounting Management of the Administrative Management Center; the projectwas developed under the prototyping software development methodology that allowed to develop applicationmodels with basic functionality without including all the logic or characteristics of the finished model. Representativefindings are presented in relation to the development of skills and competences from the interactionwith educational simulators, reducing both the possibilities of making mistakes in practice and the undesiredsocial and individual consequences that could be triggered in a real scenario.